Pemilihan Duta Pendidikan Fakultas Menggunakan Metode Simple Additive Weighting (SAW) - Evi Fadilah (Program Studi Sistem Informasi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Raden Fatah Palembang, 2021)
The selection of faculty student ambassadors at Universitas Islam Negeri (UIN) Raden Fatah Palembang is a routine activity, and is a prestigious award for students. The selection of student ambassadors aims to prepare the best students at the faculty level. This event is important to be carried out objectively, because the student ambassadors are representatives of students on campus activities. In the selection process there are problems such as the assessment that is not transparent, thus giving the opportunity for the jury to give a subjective assessment of the participants. In this research, the Simple Additive Weighting (SAW) method was used to help make decisions. This research aims to build a web-based decision support system for selecting faculty student ambassadors using the SAW method. The Decision Support System is used to assist the jury and the committee team in conducting the participant assessment process based on predetermined criteria so that it can assist in making an objective assessment. In this research there are 12 criteria used. This research resulted in a decision support system that can be used to assist the jury and committee in conducting an objective assessment process. The final result of the selection process is carried out by the system using the SAW method for the process of calculating the participant's value.